Integrating Islamic Social Funds in Sharia Banking for Empowering Indonesia’s Productive Poor - Khotibul Umam; Berlian Widya Tama; Khotibul Umam; Berlian Widya Tama (Journal of Central Banking Law and Institutions, 2026)
The enactment of Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (the DSFS Law) expands the role of Sharia banks beyond collecting social funds to managing and distributing them. However, challenges remain, including limited financial inclusion, limited use of social contracts such as qardh al-hasan, and underutilisation of commercial contracts like salam and istishna, which could benefit the micro, agricultural, and manufacturing sectors. This study examines the compatibility of Islamic social funds (ISF) with a bank’s role as a financial intermediary and with the expected function of Sharia banking in financing a productive poor society. This study uses normative legal research, emphasising secondary data, and employs three approaches: the statutory approach, the conceptual approach, and the comparative approach. The DSFS Law (Law No. 4/2023) provides a clear legal basis for Sharia banks and Sharia business units not only to collect but also to manage and distribute ISF. The DSFS Law broadens Sharia banks’ role in (ISF). However, gaps remain in waqf management and zakat coordination, creating challenges for integration with Sharia banking. To overcome this, more substantial regulatory alignment and support from Bank Indonesia (BI) and the Financial Services Authority (Otoritas Jasa Keuangan/OJK) are needed to fully connect sharia banks’ intermediation role with ISF.